Disentangling radical right populism, gender, and religion: an introduction. Issue 4 (4th July 2022) - Norocel, Ov Cristian; Giorgi, Alberta
ABSTRACT: This Special Issue provides diverse multidisciplinary entry points that convey the multi-layered complexity of the interactions between radical right populism, gender issues, and religious questions. It fills a gap in the scholarship dealing with the political and social manifestations of radical right populism. From a theoretical point of view, the connections between radical right populism and gender and between radical right populism and religion, respectively, have received growing scholarly attention. The present Special Issue bridges these separate lines of inquiry, concentrating on how issues of gender and religion are jointly addressed in radical right populist discourses. The articles in this Special Issue provide the first in-depth and comparative understanding of the entanglements of gender and religion in radical right populist ideology, explore the active role of religion in the populist discourse, and invite to combine the analysis of the political sphere with the analysis of occurrences in the broader society.